Recognition and Diagnosis of Neuro-Ichthyotic Syndromes - Rizzo, William B. (Semin Neurol, 2012)
The combination of neurologic disease and ichthyosis defines a heterogeneous group of rare inherited disorders that present in infancy through early adulthood. Although affected patients share the cutaneous feature of ichthyosis, there is variability in the nature and severity of neurologic disease. Impaired cognition, spasticity, sensorineural deafness, visual impairment, and/or seizures are the primary neurologic findings. Most of these disorders are caused by genetic defects in lipid metabolism, glycoprotein synthesis, or intracellular vesicle trafficking. The clinical features of some of the neuro-ichthyoses are distinct enough to allow their clinical recognition, but confirmatory biochemical or genetic tests are necessary for accurate diagnosis. Treatment of the ichthyosis is largely symptomatic, and except for Refsum’s disease, there are no effective pathogenesis-based therapies for the neurologic disease.